The relationship between peer interaction and adolescent’s dating behavior aged 15 – 24 years in Indonesia (IDHS 2017 analysis) - Fahdilla, Noviyanti; Wahab, Abdul; Padmawati, Retna Siwi (BKM Public Health and Community Medicine, 2023)
Purpose: This study aims to determine the relationship between peer interaction and risky dating style behavior in adolescents aged 15-24. Methods: A quantitative method using secondary data from the Indonesia Demographic and Health Survey (IDHS) 2017 with a cross-sectional study design. The research sample population used in this study includes male and female adolescents aged 15-24 years in Indonesia who are unmarried and currently or have been in a relationship. Results: The behavior of adolescent dating style in Indonesia is in the low-risk dating style category, including holding hands and hugging. Bivariate analysis showed that there was a relationship between risky peer interactions and high-risk adolescent dating behavior, including kissing, touching and being touched on sensitive body parts, and sexual intercourse (p<0.05 and OR=1.42). The multivariable results showed that no external variables interfere with the relationship between peer interactions and dating style in adolescents. Conclusion: Peer interaction in risky reproductive health issues is associated with high-risk adolescent dating behavior, including kissing, touching sensitive areas, and sexual intercourse. Promotion and increasing education for adolescents related to reproductive health issues need to be done to minimize the incidence of high-risk dating styles among adolescents.